A ordem dos constituintes sintáticos na formação de sentenças em Libras na perspectiva da Linguística Funciona - Olizaroski, Iara Mikal Holland (2017)
Between many inquiries that have been challenging the scientific community from a grammatical point of view, one, to which there is no consent yet, is related to the order of the constituents of the sentences produced in the Brazilian Sign Language (Libras), because, although it is the language of deaf people in Brazil since 2002, official by the means of the Law nº 10.436 and regulated through the decree nº 5.626 in 2005, one of the big problems for its use and linguistic description refers to the little knowledge that oneself has regarding the organization and structuring of its sentences. Thus, discussing the Libras in a linguistic-theoretical perspective, some syntactic problems emerge, which bring many inquiries, being three of them the ones that guide this research, namely: (i). Which are the syntactic pattern accepted in Libras? (ii) What motivates and/or licenses these patterns? And; (iii) The syntactic orders shown in Libras sentences would be, exclusively, due to its visuospatial modality, with the kind of verb that can be shown? Thus, with the purpose of finding answers to this inquiry, we traced, as the main objective, the reflection over the syntagm organization in sentences produced in Libras . On the perspective of reaching this objective, we based the research on the theoretical assumptions of the Functional Linguistic, which tries to explain the sentence structure according its linguistic function. Being this way, we start from the Greenberg‟s (1963) postulates, to whom the great majority of languages have diverse variable orders, but only one as dominant, and they can be distributed in SVO, SOV, VSO, VOS, OSV or OVS: we passed, among others, by Hopper and Thompson (1980), with the intention of verifying if the conceived transitivity by the means of a continuum scale of ten parameters influence in the syntactic constituent organization of sentences in Libras; we sought, as well, in Chafe (1979), Borba (2002) and Ferreira Brito (2010) punctual inquiries referring to verb with the syntactic-semantic value and the visuospatial modality classification. In this perspective, as methodology we adopted the basic research, the bibliographical revision type and the qualitative nature. As technic and procedure of collecting data the selection of sentences in Portuguese Language in the Portuguese Corpus/2006, submitting them, after their preparation, to a deaf informer interpretation, which has remitted us to a field research. The transition of these sentences to gloss-Libras resulted in a Parallel Corpus constituted of 114 sentences, by means of which we could perform syntactic analyses observing the syntagm organization of the sentences produced in Libras our main objective. As result of this research, we have verified that, in Libras, the SVO, SOV and OSV patterns tend to manifest themselves, being the transitivity a strong motivation and/or licensing motivation for these patterns, as well as the visuospatial modality with the syntactic-semantic value of the verb, because we realized, during the reflections, that the same kind of verb in classification in Libras can present distinct orders in the same transitivity pole, which is, low transitivity sentences, containing process verbs or state verbs and, in Libras, non-directional based to the body, tend, more commonly, to present the SVO pattern. On the other hand, the high transitivity sentences containing action-process and action verbs and, in Libras, irreversible directional, reversible directional, classifiers, non-directional based on the body, that incorporate the object and instrumental tend to present the SVO, SOV and OSV patterns. Thus, despite the disparity in classification in Libras these verbs coincide in syntactic-semantic value as well as in the sentential transitivity pole. This led us to deduce that only the kind of verb in its visuospatial modality cannot be preponderant motivator of the syntactic order constituents of sentences produced in Libras